Unveiling the Essence: Exploring the Lived Experiences of Essu-Guiuan Instructors Using Modular Distance Learning as Mode of Instruction: A Phenomenological Study - MAGALONA, JASON D.; CELIS, JARED HAREM Q. (Journal of Ecohumanism, 2024)
This study explores and develops a phenomenological understanding of the lived experiences of instructors using modular distance learning (MDL) as a mode of instruction. It aims to examine their views on MDL, the challenges they encounter, and their coping mechanisms. The study utilized a phenomenological inquiry approach, conducting in-depth interviews with nine selected instructors from ESSU-Guiuan. The collected data underwent thematic analysis to identify key themes and sub-themes. The findings reveal that instructors generally view MDL as a flexible and convenient mode of instruction, offering practical solutions for accessible education, reaching a wider range of learners, and integrating new instructional technologies. However, concerns regarding the quality of education and issues related to academic integrity are raised. Challenges faced by instructors in MDL include developing effective course materials, limited internet connectivity and technological resources, managing heavy workloads, and addressing communication barriers. To cope with these challenges, instructors employ various strategies such as collaboration, time management, engaging in unwinding practices, and maintaining professionalism when dealing with challenging student behavior. The study emphasizes the need to address the quality of education in MDL, promote academic integrity, and support instructors in managing their workload and communication barriers. Recommendations include enhancing training and support for instructors, improving access to technology and internet connectivity, establishing guidelines for academic integrity, fostering collaboration and support among instructors, and implementing effective time management strategies.